Proposed plant design for the manufacture of liquid and solid carbon dioxide - Carating, Elizabeth G.; Estanislao, Teresita R.; del Rosario, Moises Edgar B. Jr. (Diliman, Quezon City College of Engineering, 1963)
This report intends to furnish substantial data in the careful study of the feasibility of putting up a carbon dioxide plant in the Philippines.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Chemical industry; Carbon dioxide industry